'Exit Jesus': Relating to the Exegesis and the Creative/Production Components of a Research Thesis - Milech, Barbara; Schilo, Ann (Griffith University, 2004)
In the early 90s a visiting scholar at Curtin University applied through the School of Communication and Cultural Studies to enroll as a doctoral student whose project would be a novel plus exegesis. That application was denied, as University regulations for research degrees couldn't accommodate alternate forms of theses. This "failure, however, motivated a double success. First, the University established two Humanities research degrees that accommodated alternate forms of research theses - a Master of Creative Arts (1997) and a Doctor of Creative Arts (1998). Second, the University later revised its regulations in ways that enabled a wide range of exegesis-plus-production forms of theses across the University. Key to the success of such programs is an understanding of the relationship of the exegesis and creative/production components of a thesis. It is a relationship far from obvious - witness the Master of Creative Arts student who, learning that she had to do an exit jesus, feared she would be crucified. Drawing on the history of establishing alternate forms of research theses at Curtin University, and on lessons provided by successful MCA and DCA theses (creative writing, visual arts, journalism, etc.), this paper explores the relationship of the exegesis and creative/production components of a research thesis. It argues that the two best can be seen as complementary articulations (outcomes) of a single research question (and related set of research objectives). It also canvasses the importance and difficulties of students understanding this relationship, as well as some best-practice models for assisting them.